The Longitudinal Relationship Between eHealth Literacy, Health-Promoting Lifestyles, and Health-Related Quality of Life Among College Students: A Cross-Lagged Analysis - Li, Shaojie; Cui, Guanghui; Zhou, Feixiang; Liu, Siyue; Guo, Yicong; Yin, Yongtian; Xu, Huilan (Frontiers in Public Health, 2022)
Objectives This study aimed to explore the longitudinal associations between eHealth literacy, health-promoting lifestyles, and health-related quality of life (HRQoL) among college students. Methods From December 2019 (T1) to December 2020 (T2), we administered the eHealth literacy scale, Short-Form Health Survey (SF-12), and Short-Form Health-Promoting Lifestyle Profile Scale to 1,181 college students in Jinan, China. Participants were recruited for 12 months for the two-stage survey. Results Stable positive correlations were shown between eHealth literacy, health-promoting lifestyles, and HRQoL across time. The cross-lagged analysis showed that eHealth literacy at T1 predicted health-promoting lifestyles at T2 (β = 0.080, P = 0.006); however, health-promoting lifestyles at T1 did not predict eHealth literacy at T2 (β = −0.026, P = 0.499). HRQoL at T1 predicted health-promoting lifestyles at T2 (β = 0.147, P < 0.001); however, similar to the eHealth literacy finding, health-promoting lifestyles at T1 did not predict HRQoL at T2 (β = 0.045, P = 0.142). eHealth literacy was also bi-directionally associated with HRQoL, and the prediction effect of eHealth literacy at T1 to HRQoL at T2 (β = 0.078, P = 0.008) was slightly higher than the prediction effect of HRQoL at T1 to eHealth literacy at T2 (β = 0.074, P = 0.023). Conclusion eHealth literacy and HRQoL may be antecedents for college students' health-promoting lifestyles. There may be significant bi-directional relationships between eHealth literacy and HRQoL.